China and climate change: just transition and social inclusion - Yang, L; Walker, R (Cogitatio, 2024)
China aims to transition from a carbon‐intensive economy to carbon neutrality before 2060. Although climate change policies commenced in 2007, this goal remains extremely challenging. Reporting on China’s progress, the articles in this issue refer to three concepts. Ecological civilization is a political construct framing China’s policy response to climate change and environmental degradation; its “thin” version refers to sustainable development and modernisation, but it also describes a higher form of civilization to replace industrial society. Environmental authoritarianism describes a top‐down system of governance or policy implementation that engages in minimal public participation; several of the articles report China’s green policies to be of this type. Just transition is a multifaceted evaluative concept employed in most of the articles to comment on the process or outcome of China’s climate change policies. The policy context is explained, before reviewing results from authors’ application of these concepts and offering a summary conclusion.